Numerical study of the aerodynamics of time-trial cycling helmets - Beaumont, F.; Taiar, R.; Polidori, G.; Zaidi, H.; Grappe, F. (Instrumentation Mesure Métrologie, 2019)
The aerodynamic drag of three different time-trial cycling helmets is analyzed numerically from two different cyclist head positions. Computational Fluid Dynamics (CFD) methods were used to investigate the detailed airflow patterns around the cyclist for a constant velocity of 15m/s without wind. CFD simulations were used to study the aerodynamic drag of the cyclist/helmet system which is closely related to the distribution of shear and pressure coefficients. We show that for a given head position, the helmet shape, by itself, has a weak effect on a cyclist`s aerodynamic performance (<1.5%). However, by varying head position, a cyclist significantly influences aerodynamic performance, the maximum difference between both positions being about 6.4%. CFD results have also shown that both helmet shape and head position significantly influence drag forces, pressure and wall shear stress distributions on the whole cyclist`s body due to the change in the near-wake behavior and in location of corresponding separation and attachment areas around the cyclist